Laundry detergents containing silicone

JP2026533993APending Publication Date: 2026-10-14DOW GLOBAL TECHNOLOGIES LLC +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026514495
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-18
Filing Date
2024-09-13
Publication Date
2026-10-14

Smart Images

  • Figure 2026533993000001_ABST
    Figure 2026533993000001_ABST
Patent Text Reader

Abstract

water, and Formula I [wherein R 1 and R 2 are C 1~16 alkyl groups, R 1 and R 2 have a total carbon atom count of 7 to 17, MM + is a cation, and x is 1 in 95 to 100 mol% of the alcohol ethoxysulfate surfactant] alcohol ethoxysulfate surfactant (I), a fabric softening silicone, and a modified carbohydrate polymer, the laundry detergent formulation, wherein the modified carbohydrate polymer comprises a cellulose ether base material, the cellulose ether base material being of Formula II (II); [wherein each R3 is independently selected from the group consisting of C1 to C7 alkyl groups, and the modified carbohydrate polymer has a Kjeldahl nitrogen TKN of 0.75 to 3 wt%], a quaternary ammonium moiety, and C 16 alkyl group and C 16 alkyl glycidyl ether residue, functionalized with a hydrophobic substituent selected from the group consisting of, the modified carbohydrate polymer comprises 0.005 to 1.5 wt% of the hydrophobic substituent based on the weight of the cellulose ether base material, and the cellulose ether base material has a molecular weight MW of more than 1,000,000 Daltons. A laundry detergent formulation is provided. 【Chemical Formula 1】 JPEG2026533993000027.jpg59170
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to laundry detergent formulations. Specifically, the present invention relates to laundry detergent formulations comprising water, Formula I

[0002]

Chemical Formula

[0003]

Chemical Formula

[0004] Laundry detergent formulations typically contain anionic surfactants, which are the primary foaming agents, along with secondary surfactants. Alkyl ethoxysulfate anionic surfactants (e.g., alcohol ethoxysulfate surfactants) have established uses in a variety of laundry detergent formulations. However, conventional AES anionic surfactants are associated with undesirable 1,4-dioxane content. Regulatory authorities are increasingly restricting the amount of 1,4-dioxane that may be present in consumer products. For example, New York State bans all but trace amounts of 1,4-dioxane in cleaning products. Typically, consumer products must contain less than parts per million (ppm) of 1,4-dioxane by weight to comply with regulations. One possible cause of unintentional incorporation of 1,4-dioxane into consumer products is the inclusion of alkyl ethoxysulfate anionic surfactants.

[0005] The incorporation of 1,4-dioxane into conventional AES surfactants is thought to occur at multiple points in time. The first point of 1,4-dioxane formation in conventional AES surfactants is thought to occur during the sulfation process of alcohol ethoxylates to produce alcohol ethoxysulfates. Ethoxylated alcohol intermediates for the production of conventional alcohol ethoxysulfate surfactants are typically produced via ethoxylation (i.e., the reaction of alcohol with ethylene oxide), which results in the distribution of alcohol ethoxylate oligomers. Under the sulfation process conditions during the production of conventional AES surfactants, 1,4-dioxane is thought to be formed. The second point of 1,4-dioxane formation related to conventional AES surfactants is thought to occur during the handling and processing of conventional AES surfactants. Handling and processing of conventional AES surfactants often involve acidic conditions at ambient temperature or high temperatures. Prolonged exposure of conventional AES surfactants and their alcohol ethoxylate precursors to acidic environments can lead to 1,4-dioxane formation. Furthermore, exposure to high temperatures (e.g., up to 280°C) during processing, storage, and / or handling may lead to the decomposition of conventional AES surfactants and the formation of dioxanes.

[0006] Traditionally, the 1,4-dioxane content in conventional AES surfactants and products incorporating such surfactants has been addressed by using stripping techniques. For example, if the 1,4-dioxane concentration exceeds a target threshold, a stripping process is used to remove excess 1,4-dioxane from conventional AES surfactants or products incorporating them. Stripping processes are not only expensive and time-consuming, but they also do not guarantee compliance with increasingly stringent regulatory requirements. Furthermore, since 1,4-dioxane can form over time in response to how conventional AES surfactants or products are handled and further processed, any previously applied stripping technique may be rendered ineffective by the generation of new 1,4-dioxane. As such, ensuring that products containing AES surfactants comply with appropriate regulations at the time they are sold to end consumers is a challenging task.

[0007] Therefore, there is still a need for laundry detergent formulations containing anionic alcohol ethoxysulfate surfactants that resist the formation of 1,4-dioxane both during the sulfation process for surfactant formation and when the alcohol ethoxysulfate surfactant is subsequently exposed to high temperatures up to 280°C.

[0008] This invention uses water and formula I

[0009] [ka] [In the formula, each R 1 and R 2 However, independently, C 1~16 It is an alkyl group, R 1 and R 2 The total number of carbon atoms in M ​​is 7-17. + This is -SO3 of formula I. - A laundry detergent formulation comprising an alcohol ethoxysulfate surfactant of formula I, which is a cation that balances the negative charge of the anion, and in 95-100 mol% of the alcohol ethoxysulfate surfactant of formula I, x is 1, a fabric softening silicone, and a modified carbohydrate polymer, wherein the modified carbohydrate polymer contains a cellulose ether base, and the cellulose ether base contains (i) formula II

[0010] [ka] [In the formula, each R 3 C 1~7 (ii)C 16 Alkyl and C 16The modified carbohydrate polymer is functionalized with hydrophobic substituents selected from the group consisting of alkylglycidyl ether residues, and the modified carbohydrate polymer contains 0.005 to 1.5% by weight of hydrophobic substituents based on the weight of the cellulose ether substrate, and the quaternary ammonium moiety of formula II and the hydrophobic substituents are randomly distributed throughout the entire backbone of the cellulose ether substrate, and the cellulose ether substrate has a weight-average molecular weight M greater than 1,000,000 daltons. W The present invention provides a laundry detergent formulation having a modified carbohydrate polymer containing less than 0.001% by weight of crosslinking units based on the weight of the modified carbohydrate polymer.

[0011] The present invention provides a method for attaching silicone to cotton, comprising: preparing a soiled cotton laundry; selecting a laundry detergent formulation of the present invention having a synergistic combination of an alcohol ethoxysulfate surfactant of formula I and a modified carbohydrate polymer; preparing a bath; and applying the bath and the laundry detergent formulation to the soiled cotton laundry to provide a washed cotton laundry, wherein the fabric-softening silicone is bonded to the washed cotton laundry. [Modes for carrying out the invention]

[0012] In addition to resisting the formation of 1,4-dioxane both during the sulfation process to form the alcohol ethoxysulfate surfactant of formula I, and thereafter when the alcohol ethoxysulfate surfactant of formula I is exposed to high temperatures of up to 280°C during processing, storage, and / or handling, the inventors have surprisingly discovered that a combination of such an alcohol ethoxysulfate surfactant of formula I (as described herein) and a modified carbohydrate polymer (as described herein) significantly improves the adhesion of silicone from laundry detergent to cotton fabrics during washing.

[0013] Unless otherwise specified, ratios, percentages, parts, etc., are expressed by weight (for example, "ppm" means parts per million by weight).

[0014] As used herein and in the appended claims with respect to laundry detergent formulations and alcohol ethoxysulfate surfactants of formula I, the term “solid weight” means dry weight, i.e., weight excluding any water that may be present.

[0015] As used herein, unless otherwise indicated, "molecular weight" or M W The term refers to weight-average molecular weight measured by conventional methods using conventional standards such as gel permeation chromatography (GPC) and polyethylene glycol standards. The GPC technique is discussed in detail in *Modern Size-Exclusion Liquid Chromatography - Practice of Gel Permeation and Gel Filtration Chromatography*, Second Edition, AMStriegel, WWYau, JJKirkland, DDBly; John Wiley & Sons, Inc. 2009. Molecular weight is reported herein in units of Daltons or equivalently in g / mol.

[0016] Preferably, the laundry detergent formulation of the present invention contains water (preferably 43 to 94.9% by weight (more preferably 45 to 94% by weight, even more preferably 57.5 to 85% by weight, most preferably 70 to 75% by weight) based on the weight of the laundry detergent formulation), and an alcohol ethoxysulfate surfactant of formula I (preferably 0.01 to 35% by weight (more preferably 0.1 to 20% by weight, even more preferably 1 to 15% by weight, most preferably 2.5 to 10% by weight) based on the weight of the laundry detergent formulation),

[0017] [ka] In the formula, each R 1 and R 2 Independently, C 1~16 Alkyl alkyl group (preferably C1~15 alkyl group, more preferably C 1~14 Alkyl alkyl groups, most preferably linear C 1~13 ) and R 1 and R 2 The total number of carbon atoms in is 7 to 17 (preferably 10 to 16, more preferably 11 to 15, even more preferably 11 to 13, most preferably 11 to 13) (preferably R 1 and R 2 (is a linear alkyl group), more preferably R 1 R is a methyl group, 2 is a straight chain C 10~12 It is an alkyl group, most preferably R 1 R is a methyl group, 2 is a straight chain C 10 M (is an alkyl group) + -SO3 in Equation I - A cation that balances the negative charge of anions (preferably M + (where x is a cation selected from the group consisting of nitrogen-containing cations (e.g., ammonium cations), metal cations (e.g., alkali metal cations, alkaline earth metal cations), boron-containing cations, and phosphorus-containing cations, more preferably ammonium cations, alkali metal cations, and alkaline earth metal cations, even more preferably ammonium cations, sodium cations, and calcium cations, most preferably sodium cations), and x is 1 in a formula I alcohol ethoxysulfate surfactant of formula II in an amount of 95-100 mol% (preferably 96-100 mol%, more preferably 97-100 mol%, most preferably 97.5-100 mol%) of a cyclic branched alcohol ethoxylate of formula II (preferably, 13The composition comprises a fabric softening silicone (preferably 0.05% to 12% by weight (preferably 0.1% to 10% by weight, more preferably 1 to 7.5% by weight, most preferably 3 to 7% by weight), based on the weight of the fabric care composition, and a modified carbohydrate polymer (preferably 0.5% to 10% by weight (preferably 0.1% to 8% by weight (more preferably 0.5% to 5% by weight, most preferably 2 to 3% by weight), based on the weight of the laundry detergent formulation), wherein the modified carbohydrate polymer comprises a cellulose ether substrate, and the cellulose ether substrate is (i) Formula II

[0018] [ka] [In the formula, each R 3 C 1~7 Alkyl alkyl group (preferably C 1~4 (ii)C 16 Alkyl and C 16 Alkylglycidyl ether residue (preferably C 16The modified carbohydrate polymer is functionalized with hydrophobic substituents selected from the group consisting of alkyl groups, and the modified carbohydrate polymer contains 0.005 to 1.5% by weight (preferably 0.1 to 1.1% by weight, more preferably 0.3 to 0.8% by weight, most preferably 0.4 to 0.6% by weight) of hydrophobic substituents (measured by GC-MS similar to ASTM method D-4794) based on the weight of the cellulose ether substrate, and the quaternary ammonium moiety of formula II and the hydrophobic substituents are randomly distributed throughout the backbone of the cellulose ether substrate. The cellulose ether base material has a weight-average molecular weight of over 1,000,000 daltons (preferably 1,100,000 to 4,000,000 daltons, more preferably 1,200,000 to 2,000,000 daltons, most preferably 1,300,000 to 1,600,000 daltons), and the modified carbohydrate polymer has crosslinking units of less than 0.001% by weight (preferably less than 0.0001% by weight, more preferably less than 0.00001% by weight, most preferably less than the detection limit).

[0019] Preferably, the laundry detergent formulation of the present invention contains 43% to less than 94.9% by weight (preferably 45 to 94% by weight, more preferably 57.5 to 85% by weight, most preferably 70 to 75% by weight) of water based on the weight of the laundry detergent formulation, and more preferably, the laundry detergent formulation of the present invention contains 43% to 94.9% by weight (preferably 45 to 94% by weight, more preferably 57.5 to 85% by weight, most preferably 70 to 75% by weight) of water based on the weight of the laundry detergent formulation, and the water is at least one of distilled water, deionized water, and industrial soft water. Even more preferably, the laundry detergent formulation of the present invention contains 43% to 94.9% by weight (preferably 45 to 94% by weight, more preferably 57.5 to 85% by weight, most preferably 70 to 75% by weight) of water based on the weight of the laundry detergent formulation, and the water is distilled and deionized. Most preferably, the laundry detergent formulation of the present invention contains 43 to 94.9% by weight (preferably 45 to 94% by weight, more preferably 57.5 to 85% by weight, most preferably 70 to 75% by weight) of water based on the weight of the laundry detergent formulation, and the water is distilled, deionized, and industrially soft to avoid the introduction of undesirable metal ions into the laundry detergent formulation.

[0020] Preferably, the laundry detergent formulation of the present invention contains, based on the weight of the laundry detergent formulation, 0.01% to less than 35% by weight (preferably 0.1 to 20% by weight, more preferably 1 to 15% by weight, most preferably 2.5 to 10% by weight) of an alcohol ethoxysulfate surfactant of formula I, where each R 1 and R 2 Independently, C 1~16 Alkyl alkyl group (preferably C 1~15 alkyl group, more preferably C 1~14 Alkyl alkyl groups, most preferably linear C 1~13 ) and R 1 and R 2 The total number of carbon atoms in is 7 to 17 (preferably 10 to 16, more preferably 11 to 15, even more preferably 11 to 13, most preferably 11 to 13) (preferably R 1 and R 2is a linear alkyl group, more preferably R 1 R is a methyl group, 2 is a straight chain C 10~12 It is an alkyl group, most preferably R 1 R is a methyl group, 2 is a straight chain C 10 (It is an alkyl group), M + -SO3 in Equation I - A cation that balances the negative charge of anions (preferably M + (where x is a cation selected from the group consisting of nitrogen-containing cations (e.g., ammonium cations), metal cations (e.g., alkali metal cations, alkaline earth metal cations), boron-containing cations, and phosphorus-containing cations, more preferably ammonium cations, alkali metal cations, and alkaline earth metal cations, even more preferably ammonium cations, sodium cations, and calcium cations, most preferably sodium cations), x is 1 in an alcohol ethoxysulfate surfactant of formula I in an amount of 95-100 mol% (preferably 96-100 mol%, more preferably 97-100 mol%, most preferably 97.5-100 mol%) (preferably, 13 (Determined using the properties of the ¹¹C nuclear magnetic resonance.)

[0021] Preferably, the alcohol ethoxysulfate surfactant of formula I contains less than 9 ppm (preferably less than 8 ppm, more preferably less than 7 ppm, even more preferably less than 6 ppm, even more preferably less than 5 ppm, even more preferably less than 4 ppm, even more preferably less than 3 ppm, even more preferably less than 2 ppm, even more preferably less than 1 ppm, even more preferably less than 0.25 ppm, most preferably less than the detection limit) of 1,4-dioxane based on the solid weight of the alcohol ethoxysulfate surfactant of formula I (preferably, the 1,4-dioxane content is measured by liquid injection cryogenic gas chromatography-mass spectrometry for the organic layer and by liquid chromatography-mass spectrometry for the aqueous layer).

[0022] Preferably, the alcohol ethoxysulfate surfactant of Formula I contains less than 2 wt% (preferably less than 1.75 wt%, more preferably less than 1.5 wt%, even more preferably less than 1.25 wt%, still more preferably less than 1.1 wt%, most preferably 1 wt% or less) of the alcohol sulfate surfactant of Formula IV, based on the solid weight of the alcohol ethoxysulfate surfactant of Formula I

[0023]

Chemical Formula

[0024] Preferably, the laundry detergent formulation of the present invention contains the above-mentioned alcohol ethoxysulfate surfactant of formula I, wherein the alcohol ethoxysulfate surfactant of formula I has high thermal stability. More preferably, the laundry detergent formulation of the present invention contains the above-mentioned alcohol ethoxysulfate surfactant of formula I, wherein the alcohol ethoxysulfate surfactant of formula I has improved thermal stability. As used herein and in the appended claims, the term “enhanced thermal stability” means that when the alcohol ethoxysulfate surfactant of formula I is heated to 110°C, it contains less than 9 ppm (preferably less than 8 ppm, more preferably less than 7 ppm, even more preferably less than 6 ppm, even more preferably less than 5 ppm, even more preferably less than 4 ppm, even more preferably less than 3 ppm, even more preferably less than 2 ppm, even more preferably less than 1 ppm, and most preferably less than 0.5 ppm) of 1,4-dioxane based on the solid weight of the alcohol ethoxysulfate surfactant of formula I (preferably the 1,4-dioxane content is measured by liquid injection cryogenic gas chromatography-mass spectrometry for the organic layer and by liquid chromatography-mass spectrometry for the aqueous layer). As used herein and in the appended claims, the term “enhanced thermal stability” means that when the alcohol ethoxysulfate surfactant of formula I is heated to 280°C, it contains less than 10 ppm of 1,4-dioxane based on the solid weight of the alcohol ethoxysulfate surfactant of formula I (preferably, the 1,4-dioxane content is measured by liquid injection gas chromatography-mass spectrometry for the organic layer and by liquid chromatography-mass spectrometry for the aqueous layer).

[0025] Preferably, the laundry detergent formulation of the present invention comprises, based on the weight of the laundry detergent formulation, from 0.05 wt% to less than 12 wt% (preferably 0.1 to 10 wt%, more preferably 0.1 to 7.5 wt%, most preferably 3 to 7 wt%) of a fabric softening silicone, wherein the fabric softening silicone is selected from the group consisting of nitrogen-free silicone polymers, anionic silicone polymers, nonionic silicone polymers, and mixtures thereof. More preferably, the laundry detergent formulation of the present invention comprises, based on the weight of the laundry detergent formulation, 0.05 to 12 wt% (preferably 0.1 to 10 wt%, more preferably 0.1 to 7.5 wt%, most preferably 3 to 7 wt%) of a fabric softening silicone, wherein the fabric softening silicone is selected from the group consisting of nitrogen-free silicone polymers, anionic silicone polymers, nonionic silicone polymers, and mixtures thereof, and the fabric softening silicone is in the form of an emulsion (preferably, the silicone emulsion is a nonionic emulsion of high molecular weight polydimethylsiloxane, for example, dimethicone (and) laureth-4 (and) laureth-23.

[0026] Preferred nitrogen-free silicone polymers include nonionic nitrogen-free silicone polymers, zwitterionic nitrogen-free silicone polymers, amphoteric nitrogen-free silicone polymers, and mixtures thereof. Preferred nitrogen-free silicone polymers have the formula V, VI or VII (preferably formula V or VII),

[0027]

Chemical Formula

[0028] Preferred nitrogen-free silicone polymers include anionic silicone polymers. Anionic silicone polymers are described, for example, in The Encyclopedia of Polymer Science, volume 11, p. 765. Examples of anionic silicone polymers include silicones incorporating carboxylic acid, sulfuric acid, sulfonic acid, phosphoric acid, and / or phosphonic acid functional groups. Preferred anionic silicone polymers incorporate carboxyl functional groups (e.g., carboxylic acid or carboxylate anions). Preferred anionic silicone polymers have a weight-average molecular weight of 1,000 to 100,000 daltons (preferably 2,000 to 50,000 daltons, more preferably 5,000 to 50,000 daltons, most preferably 10,000 to 50,000 daltons). Preferably, anionic silicone polymers have an anionic group content of at least 1 mol% (more preferably at least 2 mol%). Preferably, the anionic groups on the anionic silicone polymer are not located at the terminal positions of the longest linear silicone chain. A preferred anionic silicone polymer has anionic groups at intermediate chain positions on the silicone. A more preferred anionic silicone polymer has anionic groups located at least five silicone atoms from the terminal position on the longest linear silicone chain of the anionic silicone polymer.

[0029] Preferably, the laundry detergent formulation of the present invention contains 0.5 to 10% by weight (preferably 0.1 to 8% by weight (more preferably 0.5 to 5% by weight, most preferably 2 to 3% by weight) of a modified carbohydrate polymer based on the weight of the laundry detergent formulation, wherein the modified carbohydrate polymer contains a cellulose ether base, and the cellulose ether base contains (i) formula II [wherein each R 3 C 1~7 Alkyl alkyl group (preferably C 1~4(ii)C 16 Alkyl and C 16 Alkylglycidyl ether residue (preferably C 16The modified carbohydrate polymer is functionalized with hydrophobic substituents selected from the group consisting of alkyl groups, and the modified carbohydrate polymer contains 0.005 to 1.5% by weight (preferably 0.1 to 1.1% by weight, more preferably 0.3 to 0.8% by weight, most preferably 0.4 to 0.6% by weight) of hydrophobic substituents (measured by GC-MS similar to ASTM method D-4794) based on the weight of the cellulose ether substrate, the quaternary ammonium moiety of formula II and the hydrophobic substituents are randomly distributed throughout the backbone of the cellulose ether substrate and are bonded to the cellulose ether substrate via at least one of ether bonds (e.g., ether bonds alone or ether bonds and a 2-hydroxypropyl group) and ester bonds, and the cellulose ether substrate is hydroxyethylcellulose, hydroxypropylcellulose, ethylhydroxyethylcellulose, methylcellulose, hydroxypropylmethylcellulose, hydroxyethylmethylcellulose and A cellulose ether base material is selected from the group consisting of these mixtures (preferably hydroxyethylcellulose, hydroxypropylcellulose, and mixtures thereof, more preferably hydroxyethylcellulose), the cellulose ether base material has a weight-average molecular weight of more than 1,000,000 daltons (preferably 1,100,000 to 4,000,000 daltons, more preferably 1,200,000 to 2,000,000 daltons, most preferably 1,300,000 to 1,800,000 daltons), the modified carbohydrate polymer contains less than 0.001% by weight (preferably less than 0.0001% by weight, more preferably less than 0.00001% by weight, most preferably less than the detection limit) of crosslinking units, and the modified carbohydrate polymer contains less than 0.1 moles (preferably less than 0.01 moles, more preferably less than 0.001 moles, most preferably less than the detection limit) of a quaternary ammonium moiety having formula III per mole of cellulose ether base material.

[0030] [ka] In the formula, each R 7 R is independently selected from methyl and ethyl groups. 8 C8~30 Selected from alkyl groups.

[0031] Preferably, the modified carbohydrate polymer is of formula (IX),

[0032] [ka] In the formula, y is the weight-average molecular weight M of the cellulose ether substrate. W Determined based on R 11 This is an alkyl group having 16 carbon atoms and C 16 Selected from the group consisting of alkylglycidyl ether residues, each R 12 Independently, C 1~7 Alkyl alkyl group (preferably C 1~4 The cellulose ether substrate has a weight-average molecular weight of over 1,000,000 daltons (preferably 1,100,000 to 4,000,000 daltons, more preferably 1,200,000 to 2,000,000 daltons, most preferably 1,300,000 to 1,800,000 daltons), M w The modified carbohydrate polymer has less than 0.001% by weight (preferably less than 0.0001% by weight, more preferably less than 0.00001% by weight, most preferably less than the detection limit) of crosslinking units.

[0033] Preferably, the laundry detergent formulation of the present invention further comprises additional cleaning surfactants. More preferably, the laundry detergent formulation of the present invention further comprises, based on the weight of the laundry detergent formulation, 0.01 to 35% by weight (preferably 0.1 to 20% by weight, more preferably 1 to 15% by weight, most preferably 2.5 to 10% by weight) of additional cleaning surfactants selected from the group consisting of anionic surfactants, nonionic surfactants, cationic surfactants, bipolar surfactants, and mixtures thereof. More preferably, the laundry detergent formulation of the present invention contains 0.01 to 35% by weight (preferably 0.1 to 20% by weight, more preferably 1 to 15% by weight, most preferably 2.5 to 10% by weight) of an additional cleaning surfactant based on the weight of the laundry detergent formulation, wherein the additional cleaning surfactant comprises alkylbenzenesulfonic acid or a salt thereof. Most preferably, the laundry detergent formulation of the present invention contains 0.01 to 35% by weight (preferably 0.1 to 20% by weight, more preferably 1 to 15% by weight, most preferably 2.5 to 10% by weight) of an additional cleaning surfactant based on the weight of the laundry detergent formulation, wherein the additional cleaning surfactant comprises a sodium salt of linear alkylbenzenesulfonic acid.

[0034] Preferably, the laundry detergent formulation of the present invention further comprises additives. Preferably, the laundry detergent formulation of the present invention further comprises additives selected from the group consisting of salt, builder, enzyme, corrosion inhibitor, acid, bleach, bleach catalyst, abrasive, antimicrobial agent, chelating agent, pH adjuster, buffer, rheology adjuster, structuring agent, fragrance, and mixtures thereof.

[0035] Preferably, a method for attaching silicone to cotton comprises preparing soiled cotton laundry, selecting a laundry detergent formulation of the present invention having a synergistic combination of an alcohol ethoxysulfate surfactant of formula I and a modified carbohydrate polymer, preparing a bath, and applying the bath and laundry detergent formulation to the soiled cotton laundry to provide a washed cotton laundry, wherein the fabric-softening silicone is bonded to the washed cotton laundry.

[0036] Herein, several embodiments of the present invention will be described in detail in the following examples.

[0037] [Table 1]

[0038] Synthesis S1:C 12 EO A 3-liter (L) three-necked glass round-bottom flask, equipped with an overhead, reflux condenser, and heating jacket, was used for the etherification of 1-dodecene and monoethylene glycol with the catalyst. A pitch-blade impeller was used for stirring to ensure good mixing. A reaction mixture of 551.7 grams (g) of ethylene glycol and 505.8 g of 1-dodecene was prepared and loaded into the reactor at 23°C along with 61 g of the catalyst in powder form. The impeller stirring speed was set to 400 revolutions per minute (rpm). The reactor was heated to 135°C over 30 minutes, held at 135°C for 18 hours, and then cooled to 23°C by turning off the heater. The reaction mixture was separated into the monoethylene glycol and catalyst phase and the olefin phase using a separatory funnel.

[0039] The distillation apparatus was constructed using a 1-liter round-bottom flask connected to a short-circuit distillation head with a thermometer adapter and a condenser with a vacuum adapter at the outlet. The distillation flask was heated in an aluminum block by an IKA heating and stirring plate. The olefin phase combined in the distillation pot was added, and then stirring and vacuum were applied. Significant boiling was observed, but no condensate was observed or collected. The heating block temperature was increased to 75°C, and unreacted dodecane was collected at a distillation head temperature of 25°C–50°C and a pressure of 13.3–40 pascals (Pa). The heating block temperature was gradually increased to 140°C, and an intermediate fraction containing both monoether alcohol ethoxylate and dodecene was recovered, with the head temperature increased from 50°C to 75°C at a pressure of 13 Pa. 12EO was collected at head temperatures of 70°C to 115°C and pressures of 6 Pa to 33 Pa. The heating block temperature was gradually increased to 200°C, and an intermediate fraction containing both monoether alcohol ethoxylate and diether was collected. The head temperature was increased from 115°C to 130°C at a pressure of 6 Pa. Distillation was stopped, and the diether remaining in the pot was collected. 12 The EO was then subjected to the next sulfation process to produce a sulfate anionic surfactant.

[0040] Synthesis S2:C 12 EO sulfate All chemical operations were performed under a dry nitrogen atmosphere. Before the experiment, all glassware was heated in a laboratory oven to remove any residual water. Dichloromethane (500 mL) and C prepared according to synthesis S1 were placed in a 2 L three-necked round-bottom flask. 12 EO (48.4 g, 0.21 mol, 1.0 equivalent) was added. The reaction flask was equipped with an overhead mechanical stirrer, an additional funnel, and a thermocouple. Next, chlorosulfonic acid (14.5 mL, 0.221 mol, 1.1 equivalents) was carefully loaded into the additional funnel. The reaction flask was then submerged in an ice bath and cooled to 0°C for 20 minutes. Once the reactants had cooled, chlorosulfonic acid was added dropwise to the reaction flask at a rate of approximately 1.0 mL / min over approximately 20 minutes. During the addition of chlorosulfonic acid, the reaction temperature did not exceed 5°C. After the addition, the reactants were allowed to react, and the temperature was maintained between 0 and 5°C for 3 hours. At this point, the reactants were neutralized by slowly adding aqueous NaOH solution (18.0 g of NaOH, 0.9 mol in 500 mL of water) dropwise. The addition rate was sufficiently slow so that the temperature did not exceed 5°C during the process. The addition of NaOH aqueous solution was continued until the reactants became basic. The dioxane content of the crude two-phase product was analyzed. Next, dichloromethane was carefully removed from the crude two-phase product under vacuum. A large amount of foam was observed during the removal of dichloromethane. After the removal of dichloromethane, the remaining aqueous solution was placed in a freeze-dryer to obtain the purified secondary alcohol ethoxylate sulfate product, C 12 EO sulfate was obtained as a whitish solid (47.7 grams). The purified product was used for performance and characterization tests.

[0041] Synthetic S3: ALEO1 Sulfate ALEO1 sulfate was prepared from ALEO1 using the same method described in Synthesis S2.

[0042] Synthetic S4:SA3EO Sulfate SA3EO sulfate was prepared from SA3EO using the same method described in Synthesis S2.

[0043] Synthetic S5: Hydrophobically modified cellulose ether substrate A 500 mL four-necked round-bottom flask was filled with cellulose ether substrate (27.3 g, CELLOSIZE™ QP-52,000H hydroxyethylcellulose, weight-average molecular weight approximately 1,600,000 Daltons, manufactured by The Dow Chemical Company), isopropyl alcohol (126.6 g), and deionized water (17.5 g). The flask was fitted with a nitrogen inlet connected to a 60 mL pressure-equalizing addition funnel, a rubber septum cap, a stirring paddle connected to an electric motor, and a Claisen adapter connected to a Friedrich condenser with a mineral oil foaming outlet. Next, the addition funnel was filled with hexadecylglycidyl ether (1.9 g) in isopropyl alcohol (7.5 g). The stirring paddle was fitted, and the flask's headspace was purged with a slow, steady flow of nitrogen (one bubble per second) for 1 hour to remove all entrained oxygen. Next, 1.6 g of a 50% sodium hydroxide aqueous solution was added dropwise to the flask contents over 2 minutes. After adding the 50% sodium hydroxide solution, the flask contents were stirred for 1 hour. Then, hexadecyl glycidyl ether in isopropyl alcohol solution in an addition funnel was added dropwise to the flask contents over 3 minutes. After adding the hexadecyl glycidyl ether in isopropyl alcohol, the flask contents were left to stir for 20 minutes. Next, heat was applied to the flask contents using a heating mantle. The flask contents were refluxed under nitrogen while being continuously stirred for 4.5 hours. Next, the flask contents were cooled by placing it in an ice bath while maintaining a positive nitrogen pressure inside the flask. Next, the flask contents were neutralized by adding glacial acetic acid (3.0 g) using a syringe. The flask contents were continuously stirred under nitrogen for 10 minutes. Next, the flask contents were vacuum filtered through a large frit metal Buchner funnel to recover the hydrophobically modified cellulose ether material.Next, the recovered hydrophobic modified cellulose ether material was washed in a Buchner funnel by stirring with a specified washing solvent in the funnel for 5 minutes, followed by vacuum removal of the washing solution: deionized water (36 g) in isopropyl alcohol (164 g); deionized water (20 g) in isopropyl alcohol (180 g); and then isopropyl alcohol (200 g) for drying. To impart cold water dispersibility to the final polymer, 40% glyoxal aqueous solution (0.44 g) and acetic acid (0.14 g) were added to the final drying washing solution. Next, the washed hydrophobic modified cellulose ether material was air-dried for a short time, and then dried overnight in vacuum at 50°C. The dried hydrophobic modified cellulose ether material was then sieved through a #30 mesh US standard sieve to obtain an off-white solid with a volatile matter content of 3.0% and an ash content of 4.8% (as sodium acetate). The viscosity of a 1% solution (corrected for ash and volatile substances) was measured in 6.31 seconds using a TA Instruments DHR-3 rheometer with a 40 mm, 2.0° stainless steel cone and plate sensor at 25.0°C. -1 Measurements revealed a value of 7,962 mPa·s. Degree of substitution of hydrophobic substance, DS hydrophobe It was measured at 0.006.

[0044] Synthetic S6: Hydrophobic / cationically modified carbohydrate polymer A 500 mL four-necked round-bottom flask was filled with 14.6 g of hydrophobic modified cellulose ether substrate prepared according to synthesis S5, 155.9 g of isopropyl alcohol, and 28.1 g of deionized water. The flask was fitted with a Claisen adapter connected to a Friedrich condenser having a nitrogen inlet connected to a 20 mL pressure-equalizing addition funnel, a rubber septum cap, a stirring paddle connected to an electric motor, and a mineral oil foaming outlet. Next, 10.5 g of a 70% aqueous solution of glycidyltrimethylammonium chloride (available from QUAB Chemicals under trade name QUAB® 151) was added to the addition funnel. The apparatus was slowly purged with nitrogen for 1 hour while stirring the contents of the flask to remove any entrained oxygen. After nitrogen purging was complete, 1.8 g of a 25% aqueous solution of sodium hydroxide was added to the contents of the flask over 2 minutes using a plastic syringe through a ceramic cap while stirring under nitrogen. After stirring for 1 hour, the contents of the addition funnel were added dropwise to the contents of the flask over 3 minutes. The contents of the flask were stirred under nitrogen for 20 minutes. Then, the contents of the flask were heated using a J-KEM controller at a set temperature of 55°C. The contents of the flask were refluxed under nitrogen for 1.5 hours while stirring. Then, the contents of the flask were cooled to room temperature while maintaining a positive nitrogen pressure inside the flask. Next, the contents of the flask were neutralized by adding glacial acetic acid (1.9 g) using a syringe. After stirring for 10 minutes, the cationic hydrophobic modified hydroxyethylcellulose polymer (cationic hmHEC polymer) was recovered from the contents of the flask by vacuum filtration through a metal frit-Buchner funnel. The recovered cationic hmHEC polymer was washed once each using a Buchner funnel with a mixture of isopropyl alcohol (164 g) and deionized water (36 g), a mixture of isopropyl alcohol (180 g) and deionized water (20 g), and a mixture of isopropyl alcohol (200 g), 40% glyoxal (0.44 g), and glacial acetic acid (0.14 g). The cationic hmHEC polymer was then briefly air-dried and dried overnight in a vacuum at 50°C.Next, the dried cationic hmHEC polymer was manually grouped using a mortar and pestle and screened through a #30 mesh US standard sieve to obtain 16.7 g of the cationic hmHEC polymer product. The cationic hmHEC polymer product had a volatile matter content of 2.67%, an ash content of 2.26% (as sodium chloride), and a Kjeldahl nitrogen content of 1.51%. The viscosity of a 1% solution (corrected for ash and volatile matter) was measured in 6.31 seconds using a TA Instruments DHR-3 rheometer with a 40 mm, 2.0° stainless steel cone and plate sensor at 25.0°C. -1 Measurements revealed a temperature of 4,360 mPa·s.

[0045] Synthetic S7: Hydroxyethylcellulose A pressure vessel was fitted with a mechanical stirring paddle, a nitrogen inlet, a rubber ceramic cap, and a reflux condenser connected to a mineral oil bubbler. The vessel was filled with Biofloc 94 wood pulp (24.5 g; Tembec Cellations), isopropyl alcohol (223.2 g), and distilled water (31.8 g). The vessel was purged with nitrogen for 1 hour while stirring the mixture to remove any oxygen introduced into the system. Under nitrogen, 14.2 g of 50% sodium hydroxide aqueous solution was added dropwise over 5 minutes using a syringe while stirring. The mixture was then stirred under nitrogen for 30 minutes. 30.1 g of ethylene oxide was added to the reaction vessel with continuous stirring and then sealed. The reaction mixture was heated to 75°C and stirred for 1 hour. The mixture was then cooled to room temperature, and the viscosity was optionally adjusted by adding hydrogen peroxide, neutralized with glacial acetic acid (11.1 g), and stirred for 10 minutes. The polymer product was recovered by vacuum filtration and washed five times with 250 mL of 4:1 (volume ratio) acetone / water using a Waring blender, followed by two washes with 250 mL of pure acetone. For the final acetone drying, 0.40 g of 40% aqueous glyoxal solution and 0.25 g of glacial acetic acid were added to treat the polymer product with glyoxal. The polymer product was then dried overnight in vacuum at 50°C. The 2% aqueous viscosity (corrected for ash and volatiles) of the product polymer was measured at 25.0°C using a Brookfield LVT, 30 rpm, spindle #4, and 500 mPa·s, resulting in a weight-average molecular weight of 400,000 daltons.

[0046] Synthetic S8-S9: Cationic Modified Carbohydrate Polymers A 500 mL four-necked round-bottom flask equipped with a 60 mL pressure equalization dropping funnel connected to a nitrogen inlet, a rubber ceramic cap, a stirring paddle, and an electric motor, as well as a subsurface thermocouple connected to a J-KEM controller and a Claisen adapter connected to a Friedrich condenser connected to a mineral oil bubbler, was filled with A g of hydroxyethylcellulose, B g of isopropyl alcohol, and C g of deionized water, prepared according to synthesis S7. Next, a 60 mL pressure equalization funnel was filled with D g of 70% aqueous QUAB 151 (glycidyltrimethylammonium chloride). While stirring the contents of the flask, the headspace of the flask was purged with nitrogen at a rate of approximately 1 bubble per second for 1 hour to remove entrained oxygen. The values ​​of A to D are listed in Table 1.

[0047] Next, while continuing to stir under nitrogen, 7.3 g of 25% sodium hydroxide aqueous solution was added dropwise to the contents of the flask using a plastic syringe over approximately 1 minute. After stirring the contents of the flask for 30 minutes, QUAB 151 from the addition funnel was added dropwise to the contents of the flask over 5 minutes. Next, the contents of the flask were stirred under nitrogen for 10 minutes, and then the temperature setting of the J-Kem controller was set to 55°C, and the flask was placed on the heating mantle. The contents of the flask were maintained at 55°C for 3 hours while continuing to stir under nitrogen.

[0048] Next, the contents of the flask were cooled by placing the flask in a cold water bath while maintaining a positive nitrogen pressure inside the flask. Then, 3.2 g of glacial acetic acid was added to the contents of the flask using a syringe, and the contents of the flask were neutralized by stirring for 10 minutes. Next, the contents of the flask were vacuum filtered through a large frit Buchner funnel. The filter cake was washed three times in the Buchner funnel, each time by stirring for 3 minutes with the specified washing solvent in the funnel and removing the washing solution under vacuum. The first wash was performed with a washing solvent mixture of 246 g of isopropyl alcohol and 54 g of distilled water. The second wash was performed with a washing solvent mixture of 270 g of isopropyl alcohol and 30 g of distilled water, and the third wash was performed with a washing solvent mixture of 300 g of isopropyl alcohol containing 0.4 g of 40% glyoxal and 0.1 g of glacial acetic acid. Next, the product, modified hydroxyethylcellulose, was recovered by vacuum filtration, air-dried for a short time, and then vacuum-dried overnight at 50°C.

[0049] The modified hydroxyethylcellulose obtained as a product was evaluated for Kjeldahl nitrogen content (corrected for ash and volatile matter) and TKN, and the results are shown in Table 1.

[0050] [Table 2]

[0051] Surfactant active sulfate (EO=0) content The active sulfate concentrations in the surfactants listed in Table 2 were determined using modifications of the procedures described in Turney, ME, Cannell, DW. Alkaline methylene blue method for determination of anionic surfactants and for amine oxides in detergents. J. Am. Chem. Soc., 42, 544-46 (1965) and Epton, SRA new method for the rapid titrimetric analysis of sodium alkyl sulphates and related compounds. Trans. Faraday Soc., 44, 226-30 (1948).

[0052] Number of moles of Hyamine (Mol H ) measurement Sodium dioctyl sulfosuccinate (SDOSS), control solution - 0.8 g (±0.1 mg) of sodium dioctyl sulfosuccinate of known purity (≧99%) was added to a 20 mL scintillation vial. 10 mL of deionized water was added to the vial and transferred to a 250 mL volumetric flask. This process was repeated 3 to 5 times to ensure the sample was transferred. Once the transfer was complete, the sample was diluted to 250 mL with deionized water. The flask was then stoppered and the solution was thoroughly mixed by repeatedly inverting the flask.

[0053] Methylene blue chloride solution - 0.050 g (±0.005) of methylene blue chloride was added to a 20 mL scintillation vial. The vial was filled with 10 mL of deionized water and transferred to a 1 L graduated cylinder. This process was repeated 3 to 5 times to ensure the sample was transferred. Next, the methylene blue solution was diluted to 1 L with deionized water. This solution was then transferred to a 2 L glass container. Once the transfer was complete, 10 mL of concentrated sulfuric acid and 50 g of anhydrous sodium sulfate were carefully added to the methylene blue solution and thoroughly mixed.

[0054] Hyamine 1622 solution: 1.1 grams of Hyamine 1622 were added to a 20 mL scintillation vial. The vial was filled with 10 mL of deionized water and transferred to a 1 L volumetric flask. This process was repeated 3 to 5 times to ensure the sample was transferred. The solution was then diluted to 1 L with deionized water. The solution was thoroughly mixed by repeatedly inverting the flask and then filtered into a 1 L glass bottle.

[0055] Standardization of Hyamine solution: 5 mL of sodium dioctyl sulfosuccinate solution was pipetteed into a 100 mL glass bottle. Next, 20 mL of methylene blue chloride solution and 25 mL of chloroform were pipetteed in. The 100 mL bottle was capped and shaken vigorously for several seconds. Then, 0.5 mL of Hyamine 1622 solution was titrated into the methylene blue / chloroform two-phase mixture. After each addition, the bottle was capped and shaken vigorously. The addition of Hyamine 1622 was continued at 0.5 mL intervals until the blue color of the chloroform layer (or lower layer) began to transfer to the upper layer. At this point, the titration rate of Hyamine 1622 was reduced to 0.1 mL and continued until the endpoint was reached. The endpoint was reached when the blue intensity of both layers matched. This standardization was completed in three steps. The number of moles of Hyamine 1622 was calculated using the following formula.

[0056]

number

[0057] Measurement of active sulfates in surfactants 0.9–1.1 grams of surfactant sample, weighed to the nearest 0.1 mg, were placed in a 20 mL scintillation vial. Next, 10 mL of deionized water was added to the vial, and the contents were transferred to a 250 mL volumetric flask. This process was repeated 3–5 times to ensure complete transfer of the sample. After transfer, the solution was diluted to 250 mL with deionized water. The flask was then stoppered, and the solution was thoroughly mixed by repeatedly inverting the flask. Next, 5 mL of the test sample solution was added to a 100 mL glass bottle via pipette. Then, 20 mL of methylene blue solution and 25 mL of chloroform were added to the 100 mL glass bottle via pipette. The glass bottle was capped and shaken vigorously for several seconds. Next, 0.5 mL of Hyamine 1622 solution was titrated into the methylene blue / chloroform two-phase mixture. After each addition, the bottle was capped and shaken vigorously. Hyamine 1622 was added in increments of 0.5 mL until the blue color of the chloroform layer (or lower layer) began to transfer to the upper layer. At this point, the increment of Hyamine 1622 was reduced to 0.1 mL and continued until the endpoint was reached. The endpoint was the point where the color intensity of both layers matched. Each sample was repeated three times. The active sulfate content (wt%) was calculated using the following formula.

[0058]

number

[0059] EO distribution of surfactants The distribution of EO adducts in the surfactants listed in Table 2 was determined by NMR or UHPLC-MS as described above, using the methodology described in Table 2, along with the results shown in Table 2.

[0060] Evaluation of nuclear magnetic resonance (EO) distribution characteristics (NMR) Samples of surfactants to be analyzed were prepared by dissolving the surfactant in deuterated dimethyl sulfoxide containing 0.025 M chromium(III) acetylacetate. The samples were then subjected to nuclear magnetic resonance ( 13 ¹³C NMR spectra were acquired using a Bruker AVANCE 400MHz spectrometer equipped with a 10mm cryoprobe set to 25°C, with the following parameters: 90° pulse, reverse gated decoupling, acquisition time of 1.38 seconds, and recycle delay of 6.4 seconds. 2048 scans were acquired. The data were processed with MNOVA, and the chemical shift referenced the solvent peak at 39.52 ppm. The DEPT-135 experiment was also acquired with the same parameters except for a 2.0 second recycle delay, and 2048 scans were performed. The ratios of the different EO adducts were calculated by integrating and comparing the intensities of the ethylene oxide alcohol terminal group at approximately 60–61 ppm, the ethylene oxide main chain group at approximately 69–70 ppm, the ethylene oxide terminal group ether peak at approximately 71–72 ppm, the unreacted primary alcohol peak at approximately 60–61 ppm, and the unreacted secondary alcohol peak at approximately 65–66 ppm.

[0061] Analysis of sodium lauryl ether sulfate by UHPLC-MS Ultra-high performance liquid chromatography-mass spectrometry (UHPLC-MS) conditions:

[0062] [Table 3]

[0063] Procedure: Compositions containing commercially available surfactants were analyzed by ultra-high-performance liquid chromatography-mass spectrometry (UHPLC-MS) using electrospray ionization (ESI). For analysis, stock solutions were prepared at a concentration of 25 ppm in a 50 / 50 methanol / water mixture. Alcohol ethoxylate samples were diluted twice to 1:100 in 50 / 50 methanol / water and vortexed for several seconds. These were then diluted 1:10 in 50 / 50 methanol / water to obtain a final dilution of 1:1,000. Ethal® LA-4 was the standard used for 1 mole of commercially available sodium laureth sulfate, and Ethal® LA-7 was the standard used for 3 moles of commercially available sodium laureth sulfate. Calibration standards were prepared at 10 ppm, 5 ppm, 2 ppm, and 1 ppm in 50 / 50 methanol / water.

[0064] Alkyl sulfates were diluted from a 1:1,000 preparation in 50 / 50 methanol / water to obtain a final 1:20,000 solution. POLYSTEP® BN-5 was used as a standard for alkyl sulfate analysis. The standard was prepared in 50 / 50 methanol / water at concentrations of 5 ppm, 2 ppm, 1 ppm, and 0.5 ppm.

[0065] Samples were analyzed using a Waters ACQUITY® UPLC system equipped with a Waters BEH C18 1.7 μm 1 × 50 mm column. Mass spectrometry was performed using a Waters LCT Premier TOF mass spectrometer with ESI. Measurements were performed in both positive and negative ion modes. Each sample preparation was injected three times for analysis. The ratios of different EO adducts were calculated by peak area and reported in Table 2.

[0066] [Table 4]

[0067] At least 95 mol% of the oligomer product of synthetic S2 has n = 1, and 5 mol% or less of the oligomer has n = 2 or greater. Specifically, ≥98 mol% of the oligomer product of synthetic S2 has n = 1, and 2 mol% or less of the oligomer has n = 2 or greater.

[0068] 1,4-dioxane content of surfactants The 1,4-dioxane content in the surfactants listed in Table 3 was determined, as mentioned, by liquid injection cryogenic gas chromatography-mass spectrometry (GC-MS) for the organic layer and by liquid chromatography-mass spectrometry (LC-MS) for the aqueous layer, using the methodology described below, along with the results provided in Table 3.

[0069] Gas chromatography-mass spectrometry (GC-MS) conditions for measuring 1,4-dioxane in the organic layer:

[0070] [Table 5]

[0071] Standards were prepared by adding dioxane to tetrahydrofuran (THF) and diluting it to 0.1–100 ppm.

[0072] Samples were prepared by mixing 3.3 g and 6.7 g of THF from the organic (DCM) layer of the crude process mixture, and the solution was then shaken for approximately 20 minutes. The solid was then centrifuged to the bottom, and the supernatant was placed in an autosampler vial. Additive samples were prepared by adding dioxane standards in the THF to separate samples at a concentration of 5–10 ppm.

[0073] Liquid chromatography-mass spectrometry (LC-MS) conditions for measuring the 1,4-dioxane content in the aqueous layer:

[0074] [Table 6]

[0075] The sample was injected either directly or diluted with water at a 1:4 ratio. Standards were prepared by preparing dioxane in THF stock solution and diluting it with water to 0.1–100 ppm.

[0076] Calculation of dioxane content in solids The ppm of dioxane content relative to the solid content in the sample is calculated according to the following formula.

[0077]

number

[0078] [Table 7]

[0079] Gas chromatography results for the SA3EO sulfate surfactant show a secondary alcohol with an average of 3 moles of ethylene oxide per molecule, containing 2 ppm of 1,4-dioxane in the organic phase at 110°C, indicating the potential for structures with n≧2 to produce 1,4-dioxane. Interestingly, when the inlet temperature was increased to 280°C, the dioxane content of SA3EO sulfate increased from 2 ppm to 1471 ppm of 1,4-dioxane in the organic phase. This result suggests that sulfated surfactants with n≧2 can produce observable 1,4-dioxane at 110°C, but such surfactants may be unstable at the high temperature of 280°C, which can lead to significant 1,4-dioxane formation. Similar to SA3EO sulfate, gas chromatography results for the ALEO1 sulfate surfactant show the formation of more than 9 ppm of 1,4-dioxane relative to the solid at 110°C. Furthermore, the ALEO1 sulfate surfactant also showed significant generation of 1,4-dioxane (259 ppm) at 280°C, indicating that the ALEO1 sulfate surfactant lacks stability at high temperatures. The present invention has C with n ≥ 1 at 95 mol% and n ≥ 2 at 5 mol% or less. 12 EO sulfate surfactants exhibit a low 1,4-dioxane content. Surprisingly, the C of the present invention 12 EO sulfate surfactants also exhibit extremely low 1,4-dioxane content, falling below the limit of detection (LOD) of GC and LC methods. Using LOD as a reference, this is C 12 This indicates that the dioxane content of EO sulfate is less than 1.6 ppm relative to the solid at 110°C. Interestingly, the C of the present invention 12 When the inlet temperature of EO sulfate is increased to 280°C, the 1,4-dioxane content of the material is still less than 1 ppm (i.e., 0.58 ppm), which is the C of the present invention. 12 This demonstrates that EO sulfate has increased thermal stability compared to the comparative material.

[0080] Comparative Examples CF1-CF7 and Example F1: Laundry detergent ingredients The laundry detergent formulations of Comparative Examples CF1 to CF7 and Example F1 were prepared by mixing the components in the weight proportions listed in Table 4 and adjusting the pH to 8 with sodium hydroxide as needed.

[0081] [Table 8]

[0082] Silicone adhesion to cotton fabric The adhesion of silicone from laundry detergent formulations prepared according to Comparative Examples CF1-CF7 and Example F1 to cotton fabrics was quantified using X-ray photoelectron spectroscopy, thereby obtaining quantitative elemental and chemical state information from the top 10 nm of the cotton fabric.

[0083] Using a circular die and arbor press, the cotton cloth was cut into 0.5-inch diameter discs. Then, for each laundry detergent formulation, 200 ppm (Ca 2+ :Mg 2+ 20 mL of water (3:1) was added to another 25 mL vial. 0.2 g of the laundry detergent formulations prepared according to Comparative Examples CF1-CF7 and Example F1 were added to each vial to form the washing solution. The vials were placed on a 15-stage stirring plate and stirred at 300 rpm. Three cotton discs were placed in each vial and stirred in the washing solution for 16 minutes. The cotton discs were then placed in 20 mL of 200 ppm (Ca) solution. 2+ :Mg 2+ (3:1) The mixture was transferred to a new 25 mL vial containing water and a stirring rod. The new vial was stirred for 3 minutes to rinse the cotton disc. The cotton disc was then removed from the vial and dried on a metal rack. The dried cotton disc was then sealed in a clean 25 mL vial. The cotton disc was then evaluated for silicone adhesion using XPS. The instrument parameters used are shown in Table 5. The mol% of silicone adhering to the cotton disc from the laundry detergent formulation is shown in Table 6.

[0084] [Table 9]

[0085] Table 10

Claims

1. Water and, Equation I 【Chemistry 1】 [In the formula, each R 1 and R 2 However, independently, C 1~16 It is an alkyl group, R 1 and R 2 The total number of carbon atoms in is 7 to 17, M + However, the -SO of equation I 3 - A cation that balances the negative charge of the anion, and an alcohol ethoxysulfate surfactant of formula I in which x is 1 in 95 to 100 mol% Fabric softening silicone and A laundry detergent formulation comprising a modified carbohydrate polymer, wherein the modified carbohydrate polymer comprises a cellulose ether base, and the cellulose ether base comprises (i) Formula II 【Chemistry 2】 [wherein each R 3 is independently selected from the group consisting of C 1~7 alkyl groups, and the modified carbohydrate polymer has a Kjeldahl nitrogen content TKN of 0.75 to 3% by weight, corrected for ash and volatiles], a quaternary ammonium moiety of, and (ii) C 16 alkyl groups and C 16 functionalized with a hydrophobic substituent selected from the group consisting of alkyl glycidyl ether residues, wherein the modified carbohydrate polymer comprises 0.005 to 1.5% by weight of the hydrophobic substituent, based on the weight of the cellulose ether base material, and the quaternary ammonium moiety of Formula II and the hydrophobic substituent are randomly distributed throughout the backbone of the cellulose ether base material, and the cellulose ether base material has a weight average molecular weight M of more than 1,000,000 Daltons W , and the modified carbohydrate polymer comprises less than 0.001% by weight of crosslinking units, based on the weight of the modified carbohydrate polymer, a laundry detergent formulation.

2. The laundry detergent formulation according to claim 1, further comprising an additional cleaning surfactant, wherein the additional cleaning surfactant comprises a sodium salt of a linear alkylbenzene sulfonic acid.

3. R 1 is a methyl group, R 2 is a straight chain C 10~12 The laundry detergent formulation according to claim 2, wherein the alkyl group is an alkyl group.

4. R 2 is a straight chain C 10 The laundry detergent formulation according to claim 3, wherein the alkyl group is an alkyl group.

5. The laundry detergent formulation according to claim 4, wherein the base carbohydrate polymer is hydroxyethylcellulose, and the base carbohydrate polymer has a weight-average molecular weight of 1,300,000 to 1,800,000 Daltons.

6. Each R 3 The group is a methyl group, the modified carbohydrate polymer has a Kjeldahl nitrogen content of 1.4 to 2.4% by weight, corrected for ash and volatile matter, and the hydrophobic substituent is C 16 The laundry detergent formulation according to claim 5, wherein the modified carbohydrate polymer is an alkyl group and contains 0.4 to 0.6% by weight of the hydrophobic substituent based on the weight of the cellulose ether base material.

7. The aforementioned laundry detergent compound, Based on the weight of the aforementioned laundry detergent formulation, 43 to 94.9% by weight of water and Based on the weight of the aforementioned laundry detergent formulation, 0.01 to 35% by weight of the alcohol ethoxysulfate surfactant of formula I, Based on the weight of the aforementioned laundry detergent formulation, 0.05 to 12% by weight of the fabric softening silicone and Based on the weight of the aforementioned laundry detergent formulation, 0.5 to 10% by weight of the modified carbohydrate polymer and The laundry detergent formulation according to claim 6, comprising 0.01 to 35% by weight of the additional cleaning surfactant, based on the weight of the laundry detergent formulation.

8. The aforementioned laundry detergent compound, Based on the weight of the aforementioned laundry detergent formulation, 70-75% by weight of water and Based on the weight of the aforementioned laundry detergent formulation, 2.5 to 10% by weight of the alcohol ethoxysulfate surfactant of formula I, Based on the weight of the aforementioned laundry detergent formulation, 3 to 7% by weight of the fabric softening silicone and Based on the weight of the aforementioned laundry detergent formulation, 2 to 3% by weight of the modified carbohydrate polymer, The laundry detergent formulation according to claim 7, comprising 2.5 to 10% by weight of the additional cleaning surfactant based on the weight of the laundry detergent formulation.

9. A method for attaching silicone to cotton, Prepare the dirty cotton laundry, Selecting a laundry detergent formulation according to claim 1 having a synergistic combination of an alcohol ethoxysulfate surfactant of formula I and a modified carbohydrate polymer, Prepare the bathwater, A method comprising applying the bath water and the laundry detergent mixture to the soiled cotton laundry to provide the washed cotton laundry, wherein the fabric softening silicone is bonded to the washed cotton laundry.

10. The method according to claim 9, wherein the selected laundry detergent formulation is as described in claim 8.